Predictive Approach for Energy Efficient Computation Offloading In Mobile Cloud Computing - Nikki,; Kumar, J (International Journal of Computer Sciences and Engineering, 2018)
Mobile Cloud is providing facilities of storage and remote application hosting. Several mobile applications are too computation intensive so power consumption issue is critical problem in mobile devices. Offloading feature in mobile cloud computing reduced power consumption issues of mobile devices. Existing research works have either used fixed mobile device speed or does not consider mobile device speed in estimation of local execution energy. Speed of mobile device plays a significant role in determination of local execution energy and it is affected by parallel running applications and clock frequency of mobile device. Because when there are applications running in parallel, execution speed of mobile is not fixed. In order to counter these issues, this work exploits Exponential Weighted Mean Moving Average to predict device speed according to load on mobile device. We have compared proposed work with two types of systems: Fixed CPU Speed system where CPU speed of mobile device is fixed throughout all offloading decisions, and Oracle which assumes to know exact speed of mobile device in advance. Evaluation of all systems is carried by using synthetic workloads.